Enzyme-responsive reporter molecules for selective localization and fluorescence imaging of pathogenic biofilms. Issue 23 (9th January 2017) - Aw, Junxin; Widjaja, Frances; Ding, Yichen; Mu, Jing; Liang, Yang; Xing, Bengang
Abstract : A novel enzyme-responsive reporter molecule (ERM-1) for selective localization of AmpC in pathogenic biofilms. Abstract : Pathogenic bacteria and their biofilm formation are responsible for a broad spectrum of microbial infections. A novel enzyme-responsive reporter molecule (ERM-1), which can specifically recognize AmpC β-lactamase (Bla) in drug resistant bacteria, has been developed to enable the selective localization of biofilms.